An Analysis of Political Paradox in Clan-Based Values and Fragmanted States in Somalia Federalism Formation - Hashi, Mohamed Bile (2024)
Despite general discussions and studies on the topic of federalism in Somalia and the progress of federalism in other African countries, ambiguity still surrounds the concept in Somalia. Previous research has focused on the influence of Somalia's clan politics and its unitary system of government, but there has been limited exploration of how clan politics interact with a federal framework in the country. There is little focus on federalism, clan-based politics and fragmentation, which are today's major political issues in Somalia. This study evaluated Somalia's federalism and the influence of clan-based politics on the fragmentation of the state. The objectives are to: assess how recognizing four point five clan identity in politics may serve as a valid instrument for power-sharing in the Somalia federal system; examine the rationality of federalizing Somalia and how it motivates trust and reconciliation among the nation; identify the perceptions of citizens on Somalia's current federal model and whether it accommodates diversity and preserves territorial integrity; and analyze the influence of the current federal model on secession and political fragmentation of the state. Qualitative research design that included document analysis, expert interviews, focus group discussion (FGDs) and first- hand observation of the events was used. Benadir (the capital city), Somaliland (declaring secession), and five member states (Jubbaland, South West, Hirshabeelle, Gal Mudug, and Puntland) and Somalia Diaspora have all been included in the sample. This study purposively sampled 52 individual interviewees and 158 FGD participants. Discourse and thematic analysis techniques were used to analyse the data. Coding, categorization, organization, and simplification of the analysis were done using QDA Miner Lite. The study found out that while the clan system may be effective for handling local clan traditional concerns, it can have significant constraints at the political level and it would be very unfavorable for Somalia's new federal government to endorse clan-based politics once again. The formation of Somalia's federalism was largely the result of external factors and a foreign-led agenda, and has not had a positive impact on trust and reconciliation; has exacerbated the country's tiny kinship-based diversity and is to blame for the widespread secessionist sentiments and Somalia state's political fragmentation.